Comparison of Multidetector Computed Tomography and Flat-Panel Computed Tomography Regarding Visualization of Cortical Fractures, Cortical Defects, and Orthopedic Screws. Issue 31 (August 2015) - Neubauer, Jakob; Benndorf, Matthias; Lang, Hannah; Lampert, Florian; Kemna, Lars; Konstantinidis, Lukas; Neubauer, Claudia; Reising, Kilian; Zajonc, Horst; Kotter, Elmar; Langer, Mathias; Goerke, Sebastian M.; et al.
<x xml:space="preserve">Abstract</x> Abstract To compare the visualization of cortical fractures, cortical defects, and orthopedic screws in a dedicated extremity flat-panel computed tomography (FPCT) scanner and a multidetector computed tomography (MDCT) scanner. We used feet of European roe deer as phantoms for cortical fractures, cortical defects, and implanted orthopedic screws. FPCT and MDCT scans were performed with equivalent dose settings. Six observers rated the scans according to number of fragments, size of defects, size of defects opposite orthopedic screws, and the length of different screws. The image quality regarding depiction of the cortical bone was assessed. The gold standard (real number of fragments) was evaluated by autopsy. The correlation of reader assessment of fragments, cortical defects, and screws with the gold standard was similar for FPCT and MDCT. Three readers rated the subjective image quality of the MDCT to be higher, whereas the others showed no preferences. Although the image quality was rated higher in the MDCT than in the FPCT by 3 out of 6 observers, both modalities proved to be comparable regarding the visualization of cortical fractures, cortical defects, and orthopedic screws and of use to musculoskeletal radiology regarding fracture detection and postsurgical evaluation in our experimental setting.